Pengaruh Pemberian Pupuk Osmocote Terhadap Perkecambahan 3 Genotipe Adenium - Andri David Paiki; Syukur Karamang; Purbokurniawan (Agrotek, 2017)
This study aims to find out the effect of osmocote fertilizer to the germination of three genotypes of Adenium and also to compare the germination among three Adenium varieties. Factorial experimental method was being used in this pot experiment which designed by using Factorial Randomized Group Design. First factor is the 3 types of Adenium, while the second factor is 6 dosage levels of Osmocote. The results of this research showed that the addition of various dosage of the osmocote significantly affected the germination of 3 types of adenium. The effective dosage of Osmocote for adenium germination is one gram while the white flower adenium has the best germinability.